Pharmacokinetic profile and in vivo anticancer efficacy of anagrelide administered subcutaneously in rodents - Kirsi Toivanen; Luna De Sutter; Agnieszka Wozniak; Karo Wyns; Nanna Merikoski; Sami Salmikangas; Jianmin Duan; Mikael Maksimow; Maria Lahtinen; Tom Böhling; Patrick Schöffski; Harri Sihto (Drug Delivery)
Anagrelide (ANA) is a phosphodiesterase 3A (PDE3A) inhibitor, commonly prescribed for essential thrombocythemia. It also functions as a molecular glue, inducing complex formation between PDE3A and Schlafen 12. This association either triggers apoptosis or inhibits proliferation in tumor cells, supporting its use in cancer therapy. Conventionally administered orally, ANA undergoes rapid metabolism and elimination, resulting in a short drug exposure time at the site of action. Here, we explored the pharmacokinetic profile of a subcutaneously (SC) injected ANA formulation in Sprague-Dawley rats by quantifying plasma ANA and metabolite concentrations using liquid-chromatography–tandem mass spectrometry. We further evaluated the in vivo tumor regression efficacy of orally and SC administered ANA in a patient-derived gastrointestinal stromal xenograft mouse model – UZLX-GIST2B – characterized by a KIT exon 9 driver mutation. The SC ANA exhibited extended-release plasma concentration–time profiles compared to intravenous and oral administrations. After a single administration in rats, plasma concentrations of ANA were detected up to 56 days later, and ANA metabolites up to 30 days later. The SC formulation also significantly reduced tumor volumes and demonstrated dose-dependent histological responses, nearly eradicating tumor tissue in 11 days with the highest dose. These findings suggest that the SC slow-release formulation maintains stable drug concentrations during treatment, potentially improving therapeutic efficacy at the target site.